PENDEKATAN PARTISIPATORIS DALAM PENGELOLAAN SUMBERDAYA ARKEOLOGIS DAN KEMUNGKINAN PENERAPANNYA DI KAWASAN ARKEOLOGIS GUNUNG KIDUL - Tjahjono Prasodjo (BRIN, 2000)
Basically, this paper contains an alternative presentation of a new approach in archaeological resource management, namely a participatory approach. In the future, it is believed that this approach will be more suitable to be applied and is in great demand by managers of archaeological resources. Obstacles and challenges will of course always come in your way, but the authors believe that the existing obstacles are much smaller than the final results to be obtained, namely preservation of archaeological resources as well as community empowerment both culturally, socially and economically.